Clinicopathological profile of mediastinal masses in a tertiary care hospital of Eastern India - Kr Saha, Bikram; Saha, Biswajit; Sarkar, Debasis; Chakrabarti, Srabani; Bhattacharya, Bhattacharya; Bandyopadhyay, Ramtanu (International Journal of Medical Research and Review, 2018)
Introduction:The Mediastinum is the central part of thorax where various organs are located which gives rise to various neoplastic and non- neoplastic lesions.Accurate diagnosis is important to formulate proper therapeutic strategy and predict prognosis. Studies are very few in this part of the country. Objective: To analyse presentation of patients with Meditastinal Mass and to classify according to the location of mass. Also, to document Malignant versus Non-malignant nature oflesions. Methods: Total 33 patients with mediastinal masses diagnosed by Imagingand Histopathological study were taken up consecutively in the study during one year of study. Results: of the 33 cases, 21 were male (63.6%) and 12 were female (36.4%), Male; female ratio being 1.8: 1. Age ranged from 14 years to 72 years maximum of 8 Patients (24.2%) in the 12-20 years of age group. 57% of the masses were malignant and 43% were benign. Most common lesion was Lymphoma in 10 cases (30.3%) followed by8 cases of Thymic tumours (24.2%). Metastatic Carcinoma was found in 6 patients (18.2%) followed by 3 patients of Germ cell tumours.One case each of Neurofibroma, Neurolipoma and 6 are of different less common category. Compartment wise, 9 cases (27.3%) were in Anterior Compartment, 1 (3%) case in Post Compartment, 3 case in superior mediastinum, 6 case in Middle mediastinum. Maximum cases, 14(42.5%) were occupying Multiple Compartments. Most common symptom was cough (72%). Pleural and Pericardial effusions were common complication of malignant lesions contributing 7 out of 19(36%) and 3 out of 19(17%) respectively. Conclusion: Mediastinal masses creates a diagnostic dilemma to the clinician. Uncommon cause of common symptoms like cough and common presentation of pleural or pericardial effusion may have Mediastinal mass behind the screen.